(untitled) (The Review of Diabetic Studies, 2024)
Background: Urological surgical procedures require highly specialized perioperative and postoperative nursing care to minimize complications, enhance recovery, and improve patient safety. Nurses’ knowledge, attitudes, and practices (KAP) play a pivotal role in determining the quality of care delivered in urological surgical units. This study aims to assess nurses’ knowledge, attitudes, and practices (KAP) regarding the care of patients undergoing urological surgical procedures and to examine the relationships between these domains and selected demographic variables. Methods: A descriptive cross-sectional study was conducted among nurses working in urological surgical units. Data were collected using a structured, validated questionnaire assessing knowledge and attitudes, along with an observational checklist measuring nursing practices. Descriptive and inferential statistics were applied using SPSS. Results: Most nurses demonstrated moderate to good knowledge and positive attitudes toward urological surgical care; however, notable gaps were identified in patient education and catheter-related practices. Statistically significant positive correlations were found between knowledge, attitudes, and practice scores (p < 0.05). Conclusion:Although nurses exhibited acceptable levels of competence, targeted educational interventions and standardized clinical protocols are required to strengthen evidence-based nursing practice in urological surgical settings.